Context and Spatial Nuance Inside a Neighborhood's Drug Hotspot: Implications for the Crime–Health Nexus. Issue 4 (3rd July 2016) - Curtis, Andrew; Curtis, Jacqueline W.; Porter, Lauren C.; Jefferis, Eric; Shook, Eric
Abstract : New geographic approaches are required to tease apart the underlying sociospatial complexity of neighborhood decline to target appropriate interventions. Typically maps of crime hotspots are used with relatively little attention being paid to geographic context. This article helps further this discourse using a topical study of a neighborhood drug microspace, a phrase we use to include the various stages of production, selling, acquiring, and taking, to show how context matters. We overlay an exploratory data analysis of three cohort spatial video geonarratives (SVGs) to contextualize the traditional crime rate hotspot maps. Using two local area analyses of police, community, and ex-offender SVGs and then comparing these with police call for service data, we identify spaces of commonality and difference across data types. In the Discussion, we change the scale to consider revealed microspaces and the interaction of both "good" and "bad" places. We enrich the previous analysis with a mapped spatial video assessment of the built environment and then return to the narrative to extract additional detail around a crime-associated corner store next to a community center. Our findings suggest that researchers should reevaluate how to enrich typical hotspot approaches with more on-the-ground context.